How do agricultural development projects aim to empower women? Insights from an analysis of project strategies - Johnson, Nancy L.; Balagamwala, Mysbah; Pinkstaff, Crossley; Theis, Sophie; Meinzen-Dick, Ruth S.; Quisumbing, Agnes R. (International Food Policy Research Institute, 2017)
Increasing numbers of development agencies and individual projects espouse objectives of women’s empowerment, yet there has been little systematic work on mechanisms by which interventions can enhance women’s empowerment. This gap exists because of the lack of consensus on indicators as well as the lack of attention paid to measuring the effects of different types of interventions on empowerment. This paper identifies the types of strategies employed by 13 agricultural development projects within the International Food Policy Research Institute’s Gender, Agriculture, and Assets Project Phase 2 (GAAP2) that have explicit objectives of empowering women. We distinguish between reach, benefit, and empowerment as objectives of agricultural development projects. Simply including women does not necessarily benefit them, and even activities that benefit do not necessarily empower. To identify strategies to empower women, we build on the domains included in the Women’s Empowerment in Agriculture Index (WEAI) and are working with the GAAP2 portfolio of projects to develop an empowerment metric that is applicable in the project setting (a project-level WEAI, or pro-WEAI). We have identified the following potential domains to be included in pro-WEAI: input into production decision making, control over resources, control over income, leadership, time, physical mobility, intrahousehold relationships, individual empowerment, reduction in gender-based violence, and decision making on nutrition. The GAAP2 projects address these domains through a wide variety of activities that can be grouped into four main types: (1) direct and indirect provision of goods and services; (2) forming or strengthening groups, organizations, or platforms and networks that involve women; (3) strengthening knowledge and capacity through agricultural extension, business and finance training, nutrition behavior change communication, and other training; and (4) changing gender norms through one-way awareness raising or two-way community conversations about gender issues and their implications. In general, projects with activities in more activity areas target more domains of empowerment, and most projects target a core set of six empowerment domains. With the exception of intrahousehold relationships, which is always targeted by activities designed to influence gender norms, projects target domains with different types of activities or combinations of activities. This setup suggests that there may be no one-to-one link between a specific activity and empowerment benefits, and that implementation modalities will determine whether and how an activity contributes to women’s empowerment. The effectiveness of these project strategies will be assessed using both quantitative and qualitative methods throughout the GAAP2 research project.